Peningkatan Kemampuan Kreatifitas Dikalangan Pengrajin Souvenir Dalam Meningkatkan Kualitas Produk - Abdul Mansyur; Abdul Rajab; Edy Jumady; Muklis Kanto; Zulkarnin Basir; Ahmad Anto; Hasyim Mucktar; Djamila Saleh (Universitas Maritim AMNI Semarang, 2023)
Bonto Bahari is one of the sub-districts in Bulukumba district which is a famous tourism destination in South Sulawesi. Beach tourism and the business of making phinisi boats are the attractions that are most in demand by tourists. As one of the popular tourist destinations, the business of making souvenirs as souvenirs is a business that is in great demand by the people of Bonto Bahari. The availability of wood raw materials and the skills of the community in making phinisi boat souvenirs that have been passed down for generations are important factors in the development of this souvenir business. However, in its development, the Phinisi ship souvenir business has not been maximized in sales. The use of marketing strategies by utilizing digital marketing has been carried out but limited to social media. Business actors are more focused on tourists who come to the gallery. So that this condition causes sales to depend on the number of tourists visiting Bonto Bahari. This community service activity is carried out to help business actors analyze their potential and weaknesses. By conducting training and mentoring, it is hoped that business actors will be able to better understand their potential, weaknesses and strengths and be able to develop the right strategy in developing their business.